Būluṣ ibn Rajāʾ : The Fatimid Egyptian Convert Who Shaped Christian Views of Islam - Bertaina, David, (Arabic Christianity ;, 2022)
Būluṣ ibn Rajāʾ (ca. 955-ca. 1020) was a celebrated writer of Coptic Christianity from Fatimid Egypt. Born to an influential Muslim family in Cairo, Ibn Rajāʾ later converted to Christianity and composed The Truthful Exposer ( Kitāb al-Wāḍiḥ bi-l-Ḥaqq ) outlining his skepticism regarding Islam. His ideas circulated across the Middle East and the Mediterranean in the medieval period, shaping the Christian understanding of the Qurʾan's origins, Muḥammad's life, the practice of Islamic law, and Muslim political history. This book includes a study of Ibn Rajāʾ's life, along with an Arabic edition and English translation of The Truthful Exposer.